Study of the tetraspanin 18 association with schizophrenia in a Han Chinese population. (30th July 2016) - Wu, Lin; Chen, Fengping; Wei, Jun; Shen, Yan; Xu, Qi
Abstract: A genome-wide association study of Han Chinese samples identified three single-nucleotide polymorphisms in the tetraspanin 18 (TSPAN18) gene to be associated with schizophrenia. However, the replication of the TSPAN18 association was inconsistent across studies. To explore the possible reason for poor replication, we conducted a case-control study to validate the TSPAN18 finding in an independent Chinese sample. The frequency of rs11038167 minor allele (A) was significantly higher only in female patients with thought disorder. Our result suggested that the TSPAN18 gene may be involved in the development of psychotic symptoms and contribute to clinical heterogeneity of schizophrenia. Highlights: A replication study of the tetraspanin 18 association with schizophrenia in Chinese. Association study could benefit from stratifying the sample with specific symptoms. Gender should be considered as a confounding factor in schizophrenia studies.